VOWEL CLASSIFICATION IN ENGLISH PHONETICS AND THE ROLE OF SCHWA IN ENGLISH PHONETICS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article provides a detailed exploration of vowel classification in English phonetics, focusing on the critical role of the schwa (/ə/) in the language. It begins by examining the three main features used to classify English vowels: tongue height, tongue backness, and lip rounding. The article highlights how these characteristics are essential in distinguishing between different vowel sounds. Special emphasis is placed on the schwa, which is characterized as a mid-central, unrounded vowel and often appears in unstressed syllables. The article underscores the schwa's significance in English, noting its frequent occurrence in function words and its central role in the natural rhythm of spoken English. The schwa’s involvement in vowel reduction, stress patterns, and assimilation processes illustrates its vital contribution to the fluidity and efficiency of English speech. The article concludes by emphasizing the schwa's indispensable role in communication, offering insights into how understanding its use can improve both language comprehension and pronunciation.